Characterization of prime numbers - Guimaray Huerta, Héctor Carlos (2012)
The prime numbers motivate the investigation in number theory; nowadays, does not exist a formula that allows get those numbers, and that the distribution thereof is considered random. There are methods to find whether a number is prime or composite. This article presents a characterization of prime numbers which is the complement of composite numbers.